Data for "Short-term paleogeographic reorganizations and climate events shaped diversification of North American freshwater gastropods over deep time" - Neubauer, Thomas A.; Justus Liebig University Giessen (My University, 2022)
The dataset contains species occurrence data for fossil North American freshwater gastropods from the Late Triassic to the Pleistocene. This includes information on geography, taxonomy/systematics, stratigraphy and literature sources.
Keywords: ddc:560; ddc:570